2022
DOI: 10.1200/jco.21.01536
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Stromal Tumor-Infiltrating Lymphocytes in Young, Node-Negative, Triple-Negative Breast Cancer Patients Who Did Not Receive (neo)Adjuvant Systemic Therapy

Abstract: PURPOSE Triple-negative breast cancer (TNBC) is considered aggressive, and therefore, virtually all young patients with TNBC receive (neo)adjuvant chemotherapy. Increased stromal tumor-infiltrating lymphocytes (sTILs) have been associated with a favorable prognosis in TNBC. However, whether this association holds for patients who are node-negative (N0), young (< 40 years), and chemotherapy-naïve, and thus can be used for chemotherapy de-escalation strategies, is unknown. METHODS We selected all patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 39 publications
(83 reference statements)
5
58
0
Order By: Relevance
“…Currently, the presence of residual disease after NACT is the only well-established approach to optimize postoperative treatment strategy in patients with TNBC. Recently, TILs have been confirmed as having a strong prognostic value in early TNBC patients treated with chemotherapy ( 64 )but also in early TNBC patients without chemotherapy where high TILs could identify a subset of patients with an excellent prognosis able to de-escalation strategies ( 65 ). According to our findings, increased ΔTILs after NACT might serve as an additional potential biomarker for de-escalation by defining a subgroup of patients with better prognosis and should be further validated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the presence of residual disease after NACT is the only well-established approach to optimize postoperative treatment strategy in patients with TNBC. Recently, TILs have been confirmed as having a strong prognostic value in early TNBC patients treated with chemotherapy ( 64 )but also in early TNBC patients without chemotherapy where high TILs could identify a subset of patients with an excellent prognosis able to de-escalation strategies ( 65 ). According to our findings, increased ΔTILs after NACT might serve as an additional potential biomarker for de-escalation by defining a subgroup of patients with better prognosis and should be further validated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of tumor associated M2 macrophages (M2 TAM) in the pre-operative biopsy tissues, such as CD68 or CD163 positive macrophages, have been associated with reduced responses to therapy and more frequent non-pCR results [ 28 , 29 ]. The anatomical intra-tumoral immune cell localizations (stroma vs. infiltration front vs. peritumoral location) have been shown to impact both partial response, stable disease, and metastatic properties [ 18 , 29 , 30 ]. The role of tumor infiltrating lymphocytes (TILs) and their association with PD-L1 expression and pCR after NAC have been the subject of several studies and are still being debated in clinical consensus treatment recommendations [ 1 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…While a trend toward a reduction in stromal TIL counts in the post-NAC specimens of patients with pCR has been reported in several studies [ 1 , 14 , 15 ]. High baseline TILs together with low stromal clusterin expression were associated with a higher likelihood of achieving a complete pathological response, which was independent from other clinico-pathological parameters, such as age, tumor/nodal stage or histological subtype [ 21 , 30 ]. Concerning stromal expression of epithelial mesenchymal transition proteins (EMT), Riemenschnitter et al reported that strong stromal Sox9 expression after NAC in breast cancer was associated with shortened overall survival, and stromal slug expression was significantly reduced in post-NAC surgical specimens [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…As known from former studies, TNBCs showed a higher density of TILs than other BC subtypes, probably because of their higher number of antigenic tumor variants, neoepitope load, and tumor mutational burden [ 5 ]. In TNBC, stromal TILs are considered a strong prognostic factor, and patients with a high TIL density show better survival [ 1 , 2 , 3 , 44 , 45 , 46 , 47 , 48 , 49 ]. However, in our panel, no effect of TILS on clinical outcome was observed in the group of TNBC, probably because the number of samples was too small (34 cases) to reach significance.…”
Section: Discussionmentioning
confidence: 99%